PENGARUH PRA PERLAKUAN DAN JENIS KEMASAN TERHADAP KARAKTERISTIK DAN MASA SIMPAN KERIPIK NANAS - Nursanty Nursanty; Oom Komalasari; Wenni Tania Defriyanti; Oktaf Juairiyah; Yenny Sugiarti; Sri Maryani; Efriandi Efriandi; Tri Susanto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
Pineapple is a perishable fruit, has a short shelf life which is only lasted 7 days at room temperature conditions (28oC - 30oC). To overcome this problem, it is necessary to do postharvest processing of pineapple as a form of pineapple diversification, so that it can maintain the value of pineapple sales during the pineapple season and abundant pineapple. One diversification of pineapple that can be done is to make pineapple chips. Making pineapple chips is done by 2 methods, namely making chips with pineapple that was previously in the freezer first and making chips with fresh pineapple. Characteristics of fresh fruit and pineapple chips are tested in a laboratory, including test parameters: proximate (water content, ash content, fat content, protein content and carbohydrate content), total acid, vitamin C, reducing sugar, pH, total dissolved solids and% parts which is eaten. Pineapple chip shelf life test is carried out on two treatments namely freezer (through cooling) and fresh (without freezer). Each treatment was tested with a mass stored in pp-Al foil and full Al-foil packaging. Each treatment in each package was tested for ALT-bacteria and MPN coliform. From the results of the ALT Bacterial Laboratory Test it was seen that for fresh pineapple chips and freezer pineapple chips with full aluminum foil or half aluminum foil (pp-al foil) packaging there was no difference in results where bacterial growth was still 0 (no bacteria growing, only MPN Coliform but still below the eligibility standard that is <2). This proves that pineapple chips made are suitable for consumption in a storage period of 1 month.